Texts in transit in the medieval Mediterranean - Langermann, Y. Tzvi; Morrison, Robert G. (Pennsylvania State University Press, 2016)
"A collection of essays using historical and philological approaches to study the transit of texts in the Mediterranean basin in the medieval period. Examines the nature of texts themselves and how they travel, and reveals the details behind the transit of texts across cultures, languages, and epochs"--Provided by publisher.
Keywords: Manuscripts, Medieval : Mediterranean Region; Civilization, Medieval; Transmission of texts : Mediterranean Region : History : To 1500